2019
DOI: 10.1101/626267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and distribution of antimicrobial resistance determinants ofEscherichia coliisolates obtained from meat in South Africa

Abstract: 28Objective: This study aimed to characterise antibiotics resistance of Escherichia coli isolates 29 from the formal meat sector (FMS) and informal meat sectors (INMS). 30Method: A total of 162 and 102 E. coli isolates from the FMS, and INMS respectively were 31 isolated by standard culture-based, and biochemical reactions. The isolates were further 32 confirmed by polymerase chain reaction (PCR). The disc diffusion method was used to 33 screen for antimicrobial susceptibility against 19 different antibiotics.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Beta-lactams, tetracycline and amphenicols were the most frequent multidrug resistance patterns and this agrees with the work of Hossain et al [44]. This suggests that the raw cow milk and its products is a high risk food that could possibly transfer resistant food pathogens to humans through consumption [45]. Worldwide, the consumption of raw milk [40] in both developed [48,27] and undeveloped countries is on the rise because of the health benefits to be derived.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Beta-lactams, tetracycline and amphenicols were the most frequent multidrug resistance patterns and this agrees with the work of Hossain et al [44]. This suggests that the raw cow milk and its products is a high risk food that could possibly transfer resistant food pathogens to humans through consumption [45]. Worldwide, the consumption of raw milk [40] in both developed [48,27] and undeveloped countries is on the rise because of the health benefits to be derived.…”
Section: Discussionsupporting
confidence: 87%
“…The finding agrees with the report of Sobur et al [41], that E. coli isolated from raw milk showed high resistance to tetracycline (89.44%), oxytetracycline (78.89%), Hossain et al [44] reported tetracycline resistance (70%), amoxicillin resistance (84%) and Sharma et al [39] reported tetracycline resistance of (33.34%). Jaja et al [45] reported that the E. coli isolated from meat in South Africa showed resistance to Chloramphenicol (24.5%), Ceftrioxone (20.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular confirmation of presumptive S. aureus and E. coli isolates was done by PCR using a primer pair to target the thermonuclease (Nuc) gene for S. aureus [ 14 , 38 ] and uidA gene for E. coli [ 39 , 40 ] (Figures 1 and 2 ). Quality control strains S. aureus ATCC 25923 and E. coli ATCC 25922 served as positive controls.…”
Section: Methodsmentioning
confidence: 99%